1996
DOI: 10.1128/aem.62.1.121-127.1996
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of styrene catabolism genes from Pseudomonas fluorescens ST

Abstract: A gene bank from Pseudomonas fluorescens ST was constructed in the broad-host-range cosmid pLAFR3 and mobilized into Pseudomonas putida PaW340. Identification of recombinant cosmids containing the styrene catabolism genes was performed by screening transconjugants for growth on styrene and epoxystyrene. Transposon mutagenesis and subcloning of one of the selected genome fragments have led to the identification of three enzymatic activities: a monooxygenase activity encoded by a 3-kb PstI-EcoRI fragment and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 29 publications
(33 reference statements)
5
42
0
Order By: Relevance
“…Functional analysis of styA and styB. We previously demonstrated that the 3-kb PstI-EcoRI fragment of pTPE30 conferred on E. coli transformants the ability to convert styrene into epoxystyrene (26). Our sequence data show that StyA, which is weakly homologous to POBA (48) and NAHG (50), is located approximately 900 bp downstream of the PstI restriction site.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Functional analysis of styA and styB. We previously demonstrated that the 3-kb PstI-EcoRI fragment of pTPE30 conferred on E. coli transformants the ability to convert styrene into epoxystyrene (26). Our sequence data show that StyA, which is weakly homologous to POBA (48) and NAHG (50), is located approximately 900 bp downstream of the PstI restriction site.…”
Section: Resultsmentioning
confidence: 76%
“…We determined the sequence of a 4,377-bp region (indicated by a heavy bar in Fig. 1B) and identified the genes encoding enzymes involved in the first steps of styrene catabolism (26). Computer analysis of the sequence showed the presence of four complete open reading frames, named styA, styB, styC, and styD, localized on one DNA strand and of two open reading frames, orf1 and orf2, localized on the opposite strand.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations